Haemostatic Genetic Risk Factors in Arterial Thrombosis - Simmonds, Rachel E.; Hermida, José; Rezende, Suely M.; Lane, David A. (Thrombosis and Haemostasis, 2001)
Haemostasis plays an integral role in arterial thrombotic disease. However, establishing which of the factors are risk factors has proven surprisingly difficult. Because of its technical simplicity and digital nature, the study of haemostatic polymorphisms as risk factors has grown in popularity. Once established as a risk factor, a genetic polymorphism has the potential to aid selective prophylaxis and therapy of disease. Numerous reports have now been published on polymorphisms of coagulation and fibrinolytic factors, of coagulation and fibrinolytic inhibitory proteins, and of platelet membrane glycoprotein receptors. This article describes the polymorphisms and evaluates the results of these studies using the premises of consistency of within-report genotype/phenotype/disease relationships and consistency of outcome between studies. Many studies have been only of association between polymorphisms and disease, a type of study that is prone to error. Furthermore, the collective outcome of these studies has primarily been inconsistent. It is concluded that despite the early promise of polymorphisms as risk factors, fresh approaches differing in scale and design are now required to clarify their possible importance.
Keywords: Haemostatic polymorphism; coagulation; fibrinolysis; platelet membrane glycoproteins